Trib1 Contributes to Recovery From Ischemia/Reperfusion-Induced Acute Kidney Injury by Regulating the Polarization of Renal Macrophages - Xie, Xiangcheng; Yang, Xiu; Wu, Junxia; Ma, Jilin; Wei, Wei; Fei, Xiao; Wang, Ming (Frontiers in Immunology, 2020)
Increasing evidence suggests that macrophage polarization is involved in the recovery from ischemia/reperfusion (I/R)-induced acute kidney injury (AKI), implying that the regulation of macrophage polarization homeostasis might mediate AKI recovery. Trib1 is a key regulator of macrophage differentiation, but its role in AKI remains unclear. Here, we aimed to investigate the role of Trib1 and its link with the macrophage phenotype in the process of adaptive recovery from I/R-induced renal injury. Lentiviral vector-mediated RNA interference (RNAi) was used to knock down Trib1 expression in mice, and a mouse model of moderate AKI was established by the induction of I/R injury. Renal function measurements and inflammatory factors were determined by the corresponding kits. Histomorphology was assessed by hematoxylin-eosin, Masson and PAS staining. Western blot and flow cytometry were employed for the analysis of signal transduction and macrophage phenotypes. IR-induced AKI significantly impaired renal function in mice via increasing the levels of BUN, Scr, NGAL and renal tubular epithelial cell (TEC) damage, leading to renal fibrosis from days 1 to 3. Through the adaptive self-repair mechanism, renal dysfunction recovered over time and returned to almost normal levels on day 28 after I/R intervention. However, Trib1 depletion worsened renal damage on day 3 and blunted the adaptive repair process of the renal tissue. Mechanistically, Trib1 inhibition suppressed TEC proliferation under adaptive self-repair conditions by affecting the expression of the proliferation-related proteins cyclin D1, cyclin B, p21 and p27, the apoptosis-related proteins Bcl-2 and Bax, and the fibrosis-related proteins collagen I and III. Furthermore, the M1/M2 macrophage ratio increased in the first 3 days and decreased from day 7 to day 28, consistent with changes in the expression of inflammatory factors, including TNFα, IL-6, IL-12, IL-10 and IL-13. Trib1 inhibition blocked macrophage polarization during adaptive recovery from I/R-induced moderate AKI. Our results show that Trib1 plays a role in kidney recovery and regeneration via the regulation of renal TEC proliferation by affecting macrophage polarization. Thus, Trib1 might be a viable therapeutic target to improve renal adaptive repair following I/R injury.